Comparative study between virtual planning and conventional planning for orthognathic surgery: Literature review (Research, Society and Development, 2024)
Orthognathic surgery, aimed at correcting facial asymmetries and improving maxillomandibular relationship, represents a significant intervention. Traditionally, conventional planning faces challenges of precision, leading to the emergence of virtual planning as a revolutionary innovation. This employs advanced simulation technologies, allowing detailed analysis of facial anatomy in three dimensions. When comparing both approaches, virtual planning stands out for its precise digital representation, considerably reducing the risk of errors during surgical intervention. The literature review, conducted from November 2023, focused on databases such as BVS, PubMed/Medline, Scielo, and Google Scholar. Out of 150 initial records, 80 full texts were analyzed, and 12 articles selected for review, considering the period from 2013 to 2023. The research highlights the growing importance of virtual planning in orthognathic surgery, providing benefits for both professionals and patients. The analysis of studies emphasizes the superiority of virtual planning in precision, clinical efficiency, and treatment customization. The introduction of intraoral scanners was identified as an advancement, contributing to image quality and anatomical precision. The aim of this article is to succinctly and objectively explore the clash between virtual surgical planning and conventional planning in orthognathic surgery, highlighting the advantages of virtual planning and its remarkable evolution in surgical practice. The conclusion underscores the significant transformation that digital technology represents in the field of orthognathic surgery, emphasizing the need for continuous training for the responsible application of this innovation. The combination of technological advancement and specialized knowledge promises a more effective and safe approach to orthognathic surgery, providing substantial benefits to healthcare professionals and patients.